(untitled) (Global Journal of Science Frontier Research, 2013)
An efficient in vitro regeneration system for Tori (Brassica campestris) -7 was developed from calli of hypocotyls and cotyledonary leaves. The optimum medium for callus induction was found with 0.5 mgl -1 2, 4-dichloro-phenoxyacetic acid (2,4-D). The best shooting medium contained 3.0 mgl-1 6, benzyl amino purine (BAP), 0.1 mgl -1 naphtalene acetic acid (NAA), and 5.0 mgl -1 AgNO 3 . Maximum number of shoots were produced when 0.5 mgl -1 kinetin was used, whereas the combined effect of 2.0 mgl -1 BAP, 0.1 mgl -1 NAA, and 5.0 mgl -1 AgNO 3 regenerated calli the most. The effect of AgNO 3 was found for callogenesis at 0.5 mgl -1 and for regeneration at 5.0 mgl -1 . In vitro regenerated shoots of Tori-7 developed roots on medium with 1.0 mgl -1 indole 3-butyric acid (IBA). The developed efficient in vitro regeneration protocol can be used as a baseline for Agrobacterium-mediated genetic transformation of the studied plants.